Dinasti Politik di Era Otonomi Daerah Dalam Perspektif Demokrasi - Fery Dona (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2022)
Political dynasties can be interpreted as the distribution of power based on familisme. The phenomenon of this political dynasty was often found in the era of regional autonomy. The enactment of regional autonomy is utilized by political elites to strengthen their power in the region. The phenomenon of this political dynasty certainly has a negative impact on the sustainability of democracy in Indonesia. To conduct this research, the authors used a qualitative literary research method by reviewing literature related to regional autonomy, democracy and political dynasties. Data collection techniques using documentation techniques. Then the data is analyzed through three stages, namely data condensation, data display and conclusion. Based on the research conducted, it was found that the number of political dynasties that occurred in the era of regional autonomy was increasing. What's more, the practice of political dynasties also has a negative impact on the sustainability of democracy. Because political dynasties lead to stagnation of leadership in just one group. In addition, political dynasties also tend to lead to the emergence of corruption dynasties.